G569(P) Is there an improvement in glycaemic control when paediatric patients commence on an insulin pump?. (May 2019) - Prathivadi Bhayankaram, N; Khattak, J; Riddle, M
Abstract : Background: Long-term outcomes in diabetic patients are associated with good glycaemic control. NICE recommends that insulin pump therapy is used for patients when multiple injections are impractical or inappropriate (Guideline 151, 2008). However, insulin pumps are very expensive and some previous studies do not suggest a significant improvement in glycaemic control compared with multiple injections. The aim of our study was to examine if a cohort of patients had improved glycaemic control after commencing insulin pump therapy. Methods: All paediatric patients on continuous insulin pumps at our centre were identified in November 2017. Demographic data was collected from each patient. Glycaemic control (HbA1c) was assessed at 3, 6 and 12 months prior to commencing the pump and at 3, 6, 12, 18 and 24 months after commencing the pump. Mean and median HbA1c were calculated and changes in HbA1c were analysed by gender and age when commencing the pump. Appropriate t-test was used to assess for statistically significant differences. Results: Sixty-six patients fit our inclusion criteria, with data available for forty-seven (71%) patients. Mean HbA1c at 12 months prior to commencing insulin pump was 59 mmol/L, mean HbA1c at 3 months prior to the pump was 58 mmol/L. Mean HbA1c at 6, 12 and 18 months following starting the pump was 60 mmol/L at each time point. There were no significant differences in HbA1c from 12 months prior to pump therapy to 18 months post therapy. There were no statistical differences for gender (p value 0.14 at 12 months after commencing pump) or age at commencing pump therapy (p value 0.83 12 months after commencing pump). Discussion: In our clinic, insulin pump use does not improve glycaemic control overall. How then can we justify expensive treatment with a strong demand for MDT resource? We are working to examine further how other factors such as index of multiple deprivation, number of household cohabitees, and concurrent continuous glucose monitoring use influence glycaemic control. Our findings highlight issues around patient selection for pumps, resource allocation within service, and patient support and are stimulating considerable self-examination towards how we deliver services in the future.